Pengembangan Sistem Informasi Penjualan Sparepart Mobil Berbasis Web - Herlina, Yenni (Journal of Informatics Management and Information Technology, 2023)
At present the development of information technology is very rapid. This can be seen from the use of computers in solving various problems. Advances in information technology provide great opportunities for companies or agencies to implement it as an information system. For this reason, the author chose PT. Astra Internasional Tbk–Isuzu Medan as the place to conduct research. The main discussion in this final assignment is the Car Spare Parts Sales Information System at PT. Web-based Astra Internasional Tbk–Isuzu Medan, which is a tool to help solve the problem of selling car spare parts. The observation method taken by the author is to take and collect data from PT. Astra International Tbk – Isuzu Medan. Apart from that, the author collected data from books related to the discussion that the author wanted to present and conducted questions and answers with PT employees. Astra Internasional Tbk – Isuzu Medan is concerned with the discussion. The author also read several papers related to the discussion material